Comprehensive residency-based point-of-care ultrasound training program increases ultrasound utilization in the emergency department. Issue 5 (5th February 2021) - Chen, Wei-Lung; Hsu, Chan-Peng; Wu, Po-Han; Chen, Jiann-Hwa; Huang, Chien-Cheng; Chung, Jui-Yuan
Abstract : Abstract: Point-of-care ultrasonography (POCUS) is a prompt and simple tool for the urgent diagnosis and treatment of patients in the emergency department (ED). We developed a comprehensive residency-based POCUS training program for ED residents and determined its effect on ultrasound utilization in the ED. We conducted a retrospective cohort study in the ED of a university-affiliated medical center, to evaluate a centralized residency-based POCUS training course for ED residents, which included 12 core ultrasound applications, from July 2017 to June 2018. Each application comprised a combined lecture and hands-on practice session that lasted for 2 hours. Pre-tests and post-tests, including still image and video interpretation, were performed. The use of POCUS (number of ultrasound studies performed divided by the number of patients each resident saw in 1 year) among ED residents, before and after the POCUS training course (July 2016–June 2017 and July 2018–June 2019), was calculated and analyzed using the Wilcoxon signed-rank test. Sixteen residents participated and completed the entire training course. The post-test score was significantly better than the pre-test score, by a median of 12 points ( P  = .04). Utilization of POCUS among the ED residents increased significantly, from 0.15 ultrasound studies per patient per year to 0.41 ultrasound studies per patient per year ( P  < .01), after completion of the entire training course. Increased POCUS scanning percentages over the cardiac tissue, soft tissue, abdominal region, vascular system, procedural guidance, and ocular regions were also noted after providing the curriculum. Conducting a comprehensive POCUS education program may enhance POCUS utilization among residents in the ED.